Dichter als Propheten: Religiöse Topoi in Christa Wolfs Kassandra und Franz Fühmanns Vor Feuerschlünden - Liermann, Susanne (Kirchliche Zeitgeschichte, 2007)
In two central texts of the GDR literature of the eighties, there appear prophetic figures: in Christa Wolf 's {! Kassandra} (1983) and in Franz Fühmann's {! Vor Feuerschlünden. Erfahrung mit Georg Trakls Gedicht} (1982), in which Kassandra is a seer and Trakl is described as a prophet. These texts show a parallelization between the narrators and their exemplary and ideal figures, which is remarkable for a partially non-fictional and autobiographical literature. This allows to draw conclusions about the author's self-concept regarding their authorship and literature: My hypothesis is that this self-concept is a compensation of a loss of importance and meaning that arose from growing conflicts with those in power: Like their figures, literature as a whole is becoming prophetic and the authors martyrs in that they abandon the belief in their agency. At the same time, these texts preserve the utopian perspective that characterizes the GDR literature since the fifties. Thereby, the religious topoi play two roles: to criticize those in power and to enhance the value of literature and their figures, by letting them suffer and die.